Impact of Long Noncoding RNA LINC00673 Genetic Variants on Susceptibility to Diabetic Retinopathy - Chuang, Chih-Chun; Yang, Yi-Sun; Kornelius, Edy; Huang, Chien-Ning; Hsu, Min-Yen; Lee, Chia-Yi; Yang, Shun-Fa (Frontiers in Genetics, 2022)
Long noncoding RNAs (lncRNAs) have been proven to play critical roles in diabetic retinopathy (DR). This study investigated whether the single nucleotide polymorphism (SNP) of long intergenic noncoding RNA 00673 (LINC00673) affects the clinical characteristics of diabetic retinopathy (DR). A total of three loci of LINC00673 SNPs (rs6501551, rs9914618, and rs11655237) were genotyped using TaqMan allelic discrimination in 276 and 454 individuals with and without DR, respectively. Our results revealed that LINC00673 SNP rs11655237 CT genotype (AOR: 1.592, 95% CI: 1.059–2.395, p = 0.026), CT + TT genotype (AOR: 1.255, 95% CI: 1.029–1.531, p = 0.025), and allele T (AOR: 1.185, 95% CI: 1.004–1.397, p = 0.044) yielded higher ratios in the non-proliferative diabetic retinopathy (NPDR) subgroup than in the non-DR group. Furthermore, the interval of diabetes mellitus (DM) was significantly shorter in the LINC00673 SNP rs11655237 CT + TT variant than that in the LINC00673 SNP rs11655237 wild type (10.44 ± 7.10 vs. 12.98 ± 8.34, p = 0.009). In conclusion, the LINC00673 SNP rs11655237 T allele is associated with a higher probability of NPDR development. Patients with the LINC00673 SNP rs11655237 CT + TT variant exhibited a short DM interval.